(untitled) (Indian Journal of Arid Horticulture, 2025)
The fruits of pomegranate variety "Mridula" showed double sigmoid pattern of growth and development. The length, diameter, volume and weight of fruit indicated two phases of growth: a rapid phase until 30-90 days after anthesis and there after a gradual phase until harvest. With the advancement of the fruit maturity, the percentage of the arils and aril rind ratio increases, whereas, percentage of rind and its thickness decreased continuously throughout the growth period of the fruit. Total soluble solids, TSS: acidity ratio, reducing and non reducing sugars and ascorbic acid content of the fruits increased with advancement of fruit maturity, whereas acidity after little increase in the beginning, gradually decreased with growth and development. For best dessert quality and profitable marketing fruits of pomegranate var. ’Mridula" under arid ecosystem can be harvested 120-150 days after anthesis.